Regulation of miR-29b-1/a transcription and identification of target mRNAs in CHO-K1 cells. (15th March 2017) - Muluhngwi, Penn; Richardson, Kirsten; Napier, Joshua; Rouchka, Eric C.; Mott, Justin L.; Klinge, Carolyn M.
Abstract: miR-29b and miR-29a transcript levels were reported to increase in exponentially growing CHO-K1 cells. Here, we examine the regulation of miR-29b-1/a in CHO-K1 cells. We observed that 4-hydroxytamoxifen (4-OHT) increased pri-miR-29b-1 and pri-miR-29a transcription in CHO-K1 cells by activating endogenous estrogen receptor α (ERα). DICER, an established, bona fide target of miR-29b-1/a, was shown to be regulated by 4-OHT in CHO-K1 cells. We showed that miR-29b-1 and miR-29a serve a repressive role in cell proliferation, migration, invasion, and colony formation in CHO-K1 cells. To identify other targets of miR-29b-1 and miR-29a, RNA sequencing was performed by transfecting cells with anti-miR-29a, which inhibits both miR-29a and miR-29b-1, pre-miR-29b-1, and/or pre-miR-29a. In silico network analysis in MetaCore™ identified common and unique putative gene targets of miR-29b-1 and miR-29a. Pathway analysis of identified putative miR-29 targets were related to cell adhesion, cytoskeletal remodeling, and development. Further inquiry revealed regulation of pathways mediating responses to growth factor stimulus and cell cycle regulation. Highlights: Tamoxifen increased transcription of miR-29b-1 and miR-29a in CHO-K1 cells. miR-29b-1 and miR-29a inhibit CHO-K1 viability. RNA seq identified the miR-29b-1 and miR-29a transcriptomes in CHO-K1 cells. MetaCore pathway analysis identified miR-29 target pathways in CHO-K1 cells.